Peningkatan Motivasi Belajar Siswa Melalui Pemanasan Permainan Kecil Pembelajaran PJOK di SMPN 1 Kota Kediri - Mokh Sabiq Khazimul Akhzab; Mokhamad Firdaus; Danang Kanda Riyatmojo (JOURNAL SAINS STUDENT RESEARCH, 2025)
The objective of this study is to motivate students by utilizing small-scale game-based warm-ups in Physical Education (PJOK) teaching at SMPN 1 Kota Kediri. The research method employed is Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model, which consists of two cycles. The subjects of the study are seventh-grade students at SMPN 1 Kota Kediri. Data were collected through observation, questionnaires, and documents, then analyzed using a quantitative descriptive method. The results indicate that the use of small-scale game-based warm-ups enhances student learning. This is evidenced by an increase in the percentage of students receiving academic support in the good or high category, from 47% in Cycle I to 84% in Cycle II. The conclusion of this study is that the implementation of small-scale game-based warm-ups can be an effective strategy to enhance student motivation in PJOK class.